The Effect of Psychological Crime of Virtual Bullying on Social Media on Victims Under the ITE Law - Alfarizy, Muhammad; Yusnita, Ummi; Uzma, Nur Lailatuka Syafa’atul (Begawan Abioso, 2024)
Cyberbullying takes many forms and adapts rapidly to technological developments. This study explores the psychological effects of virtual bullying on social media on victims, with the legal basis set out in Indonesia's Electronic Information and Transaction Law (UU ITE). Online bullying has become a major problem in the digital age, significantly impacting the psychological well-being of victims, and often having a more severe impact than conventional bullying. This study aims to identify the forms of virtual bullying regulated by the ITE Law, analyze the psychological impact on victims, and evaluate the effectiveness of legal protection provided by the ITE Law. Using a normative juridical approach, this research evaluates the articles in the ITE Law that are relevant to cyberbullying and relates them to the cases that occur. The results show that cyberbullying can cause various psychological disorders, including anxiety, depression, and decreased self-esteem. The ITE Law provides a strong legal framework to address these acts, with strict criminal sanctions and protection mechanisms for victims. However, the effectiveness of the ITE Law is highly dependent on consistent implementation by law enforcement as well as increased public awareness and education regarding digital ethics. This study concludes that collaborative efforts between the government, educational institutions, and communities are needed to reduce the incidence of virtual bullying and ensure that victims receive the support they need.